Carbon180 : choosing a winning strategy for carbon removal - Isaacs, Andrew M.; Cotosky, Elis Valeria Anginski (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2019)
Carbon180's co-founders are at a crossroads in reassessing their organization's future strategy and vision to drive a new carbon-conscious economy. Because Noah Deich and Giana Amador believe that 'big challenges require big thinking,' they have taken a multisector approach towards climate change solutions, working in business, policy, and research. This has resulted in some wins while at the same time challenging the resources of their small organization. Also, their funders recommend tighter focus.Carbon180 must weigh competing strategies to catalyze social change and make key decisions on whether a narrow or broad approach will best achieve the goal of reducing carbon emissions.
Originally Published In Issacs, A., & Cotosky, E. V. A. (2019). Carbon180: Choosing a Winning Strategy for Carbon Removal. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Carbon dioxide mitigation -- Case studies; Climate change mitigation -- Case studies